The Fraud under the fair value Exploratory Study - فليح, حكيم حمود (Journal of Economics and Administrative Sciences, 2015)
The research aim is to identify the concept of fair value and its measurement approaches, shed light on the concept of fraud and its forms, motives, as well as how to identify fraud under the fair value method.I have been using the program package SSPS statistical in the calculation of the research variables, and the research sample was a group of university professors and auditors working in the federal board of Supreme Audit.   The researcher has reached some conclusions, the most important; the lack of conclusive evidence about management's intent in adopting the use of fair value raises several doubts about the credibility of the statements prepared in under the fair value. Also, the use of the fair value of listed companies in the Iraqi stock Exchange may delay the issuance of financial statements in the suitable time, causes losing the interest of that statements, as the companies, with the application of historical cost, delay the preparation of financial statements and its issues.Also, the researcher suggests some recommendations: it should not sacrifice objectivity and the suitable time in exchange for information that might not be relevance for users of financial statements, as well as the necessity of prescriptive approach in the case of the adoption of any standard which requires companies to apply the fair value measurement in accounting for financial statements in order to limit the flexibility and the possibility of manipulation in financial items